The Promotion of Social Cohesion Through Education in Sri Lanka - World Bank (World Bank, Washington, DC, 2014)
The social dimensions and benefits of education are being increasingly appreciated in developed and middle-income countries. Among the many social benefits of education, promoting social cohesion in countries has become extremely important in the modern world, as global mobility of culturally diverse populations has posed challenges to the shared values, ethics and identities of societies. The instantaneous transfer of diverse and varied information through modern communications technologies has further increased the importance of social cohesion. Cohesive societies are more effective in achieving collective economic and social goals, since such societies are better at including and uniting diverse groups and forging synergy (OECD, 2001; Greaney, 2006). Five dimensions of social cohesion, belonging, inclusion, participation, recognition and legitimacy, are especially important for multi-ethnic, multi-cultural and multi-religious societies such as Sri Lanka. The education system is of central importance in promoting national unity and solidarity among the different social groups in a country. Education is a key instrument in the promotion of social cohesion through the transmission of knowledge and the shaping of attitudes of individuals towards diversity and change. Sri Lanka has initiated measures to promote social cohesion through the school curriculum, textbooks, teacher development, co-curricular and extra-curricular activities, the organization of schools, and language policy. This paper discusses these measures, and future policy options for Sri Lanka as a middle-income society.